2023
DOI: 10.3390/bios13030371
|View full text |Cite
|
Sign up to set email alerts
|

ZnO-Based Electrochemical Immunosensor to Assess Vaccine-Induced Antibody-Mediated Immunity against Wild-Type and Gamma SARS-CoV-2 Strains

Abstract: The evaluation of serological responses to COVID-19 is crucial for population-level surveillance, developing new vaccines, and evaluating the efficacy of different immunization programs. Research and development of point-of-care test technologies remain essential to improving immunity assessment, especially for SARS-CoV-2 variants that partially evade vaccine-induced immune responses. In this work, an impedimetric biosensor based on the immobilization of the recombinant trimeric wild-type spike protein (S prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Similarly, it has been found that ZnO plays an essential role in bio-conjugation between sensing materials and biomolecular species, such as viruses. 161 In a recent work, a ZnO NR based electrochemical impedimetric biosensor for detecting antibodies against the SARS-CoV-2 spike protein (in convalescent and vaccinated people) was developed by Nunez et al 162,163 The immobilization of the SARS-CoV-2 recombinant trimeric spike protein (S protein) on ZnO NR modified F-doped SnO 2 substrates for COVID-19 serology testing served as the foundation for this study. Morphological investigations were carried out which showed that the smooth surface of ZnO NRs (diameter 490 nm) became fade (covered) after SARS-CoV-2 recombinant spike protein immobilization.…”
Section: Applications In Biosensingmentioning
confidence: 99%
“…Similarly, it has been found that ZnO plays an essential role in bio-conjugation between sensing materials and biomolecular species, such as viruses. 161 In a recent work, a ZnO NR based electrochemical impedimetric biosensor for detecting antibodies against the SARS-CoV-2 spike protein (in convalescent and vaccinated people) was developed by Nunez et al 162,163 The immobilization of the SARS-CoV-2 recombinant trimeric spike protein (S protein) on ZnO NR modified F-doped SnO 2 substrates for COVID-19 serology testing served as the foundation for this study. Morphological investigations were carried out which showed that the smooth surface of ZnO NRs (diameter 490 nm) became fade (covered) after SARS-CoV-2 recombinant spike protein immobilization.…”
Section: Applications In Biosensingmentioning
confidence: 99%
“…Nanomaterials made of metal oxides, like other nanomaterials, provide a high specific surface area for immobilization. Among metal oxides, nanoparticles and nanostructures of TiO 2 , ZnO, WO 3 , and others are most often used [51,[139][140][141][142][143][144][145]. The charge transfer resistance R ct in non-faradaic EIS biosensors can tend to infinity if dielectric materials are used for immobilization [146][147][148].…”
Section: Metal Oxides and Dielectricsmentioning
confidence: 99%